Friendship, Secrecy, Transatlantic Networks and the Enlightenment: The Jefferson-Barlow Version of Volney’s Ruines (Paris, 1802) - Caron, Nathalie (Mémoires du livre / Studies in Book Culture)

(untitled) (Groupe de recherches et d’études sur le livre au Québec, 2019)
In 1802, a third English translation of Volney’s Ruines; ou, méditation sur les révolutions des empires, a work already popular among English-speaking radicals and freethinkers, appeared in Paris. The anonymous translators of the work were none other than Thomas Jefferson and Joel Barlow. Barlow’s name surfaced in 1819 whereas Jefferson’s did not until the early twentieth century. The fact that Jefferson secretly contributed to the third translation of LesRuines as well as to its circulation in the United States is an aspect of his career which, while it has not been ignored, has not been given adequate attention. The essay fleshes out knowledge of Volney and Jefferson’s friendship, traces out the story of the translation, and explores the reasons for the success of Ruins in the young United States, shedding light on the networking which allowed radical Enlightenment ideas to infuse American culture.